Die deutsche Substandivdeklination in pädagogischer Aufbereitung - Darski, Józef Paweł (Wydawnictwo Naukowe UAM, 1996)
The author finds the current and commonly acceptable division of German noun declension very complicated. Instead, he proposes only four simple rules for noun declension, with the exclusion of proper nouns and the nominalizations that receive separate treatment. Next, the author discusses noun declension in singular in cases when the learner or student only knows the gender. Subsequently, he takes into account the variation in the declension and the omission of inflectional paradigm in the sentence.